Concurrent training, determining factor for physical condition after suffering from COVID 19: case study - Velandia Cabrera, Pedro Felipe
COVID – 19, one of the strongest diseases that humanity has suffered; however, recovery processes, physical activity continues to be an important means of human health. This study designed a systematic physical exercise program based on concurrent training combining strength, endurance and aerobic capacity. Objective: describe the physical conditioning process from concurrent training for the development and improvement of physical condition after having suffered from COVID-19, case study; Method: quantitative, descriptive approach in a 40-year-old person with a medium-high level of physical fitness, with more than 5 years of training and with consequences of COVID - 19; Conclusions: it can be determined that concurrent training is an effective method for physical conditioning processes in people with consequences of COVID - 19, it is necessary to establish training loads progressively that allow improving the physical condition of the individual.